Allogeneic bone marrow–derived mesenchymal stromal cells for hepatitis B virus–related acute‐on‐chronic liver failure: A randomized controlled trial - Lin, Bing‐liang; Chen, Jun‐feng; Qiu, Wei‐hong; Wang, Ke‐wei; Xie, Dong‐ying; Chen, Xiao‐yong; Liu, Qiu‐li; Peng, Liang; Li, Jian‐guo; Mei, Yong‐yu; Weng, Wei‐zhen; Peng, Yan‐wen; et al. (Hepatology (Baltimore, Md.), 2017)
Mortality from hepatitis B virus (HBV)–related acute‐on‐chronic liver failure (ACLF) is high due to limited treatment options. Preclinical and clinical investigations have proved that treatment with mesenchymal stromal cells (MSCs) is beneficial for recovery from liver injury. We hypothesized that the outcome of HBV‐related ACLF would be improved by MSC treatment. From 2010 to 2013, 110 patients with HBV‐related ACLF were enrolled in this open‐label, nonblinded randomized controlled study. The control group (n = 54) was treated with standard medical therapy (SMT) only. The experimental group (n = 56) was infused weekly for 4 weeks with 1.0 to 10 × 105 cells/kg allogeneic bone marrow–derived MSCs and then followed for 24 weeks. The cumulated survival rate of the MSC group was 73.2% (95% confidence interval 61.6%‐84.8%) versus 55.6% (95% confidence interval 42.3%‐68.9%) for the SMT group (P = 0.03). There were no infusion‐related side effects, but fever was more frequent in MSC compared to SMT patients during weeks 5‐24 of follow‐up. No carcinoma occurred in any trial patient in either group. Compared with the control group, allogeneic bone marrow–derived MSC treatment markedly improved clinical laboratory measurements, including serum total bilirubin and Model for End‐Stage Liver Disease scores. The incidence of severe infection in the MSC group was much lower than that in the SMT group (16.1% versus 33.3%, P = 0.04). Mortality from multiple organ failure and severe infection was higher in the SMT group than in the MSC group (37.0% versus 17.9%, P = 0.02). Conclusion: Peripheral infusion of allogeneic bone marrow–derived MSCs is safe and convenient for patients with HBV‐related ACLF and significantly increases the 24‐week survival rate by improving liver function and decreasing the incidence of severe infections. (Hepatology 2017;66:209–219).